Pengaruh Penerapan Restrukturisasi Organisasi, Pemanfaatan Teknologi Informasi dan Komunikasi Serta Penyempurnaan Sumber Daya Manusia Terhadap Kepatuhan Wajib Pajak - Huda, Samsul (Jurnal Manajemen dan Kewirausahaan, 2016)
The objective of research is to provide empirical evidence about the effect of organizational restructuring practice, information and communication technology utilization, and human resource perfection on the obedience of private taxpayers at Pratama Tax Service Office of North Malang. Method of research is quantitative with survey subjected to Private Taxpayers (WPOP) who effectively registered at Pratama Tax Service Office of North Malang. Data analysis is using Structural Equation Modeling (SEM). Result of research showed empirical evidence that organizational restructuring practice was influential to or brought an impact on the increasing obedience among taxpayers. The best indicator to this variable was Internal Audit. Information and Communication Technology Utilization is influential to or delivered an impact on the increase of taxpayers obedience. The best indicator of this variable is Information Technology Based. Human resource perfection is influential to or impacting on the increasing obedience of taxpayers. The best indicator of this variable was Customer Driven. Some theories are used to support the explanation about taxpayers obedience. Among these included Planned Behavior Theory and Fiscal Psychology Theory. Both theories perceived that the policy made by the government as the holder of tax authority, and the attitude and perception of taxpayers, similarly played important role to increase taxpayers obediencehttps://doi.org/10.26905/jmdk.v4i2.552